Underpricing and Long-Term Performance: A Study on Family Firm and Non-Family Firm IPOs in Indonesia - Laylatul Inaya; Muhammad Saiful Hakim (Journal Research of Social Science, Economics, and Management, 2025)
Abstract. This study aims to determine the effect of CEO characteristics, auditor reputation, and the moderation of underwriter reputation on the level of underpricing and long-term performance of family and non-family firms in IPOs in Indonesia. The study uses data from IPO companies between 2010-2021, with 350 companies as research samples, consisting of 140 family firms and 210 non-family firms. Data was collected from secondary sources such as the OSIRIS website, IDX, Bloomberg, and Yahoo Finance. The study found that Auditor Reputation has a significant negative effect on underpricing in family and non-family firms. The level of underpricing has a significant negative effect on long-term performance in family firms. Auditor Reputation has a significant positive effect on long-term performance in family firms, but Auditor Reputation does not affect long-term performance in non-family firms. The moderation of underwriter reputation weakens the relationship between family firms and underpricing but does not affect the relationship between family firms and long-term performance. It was also found that CEO characteristics do not affect underpricing and long-term performance in family and non-family firms.